Students' Attitude to the Marketing Communications: Cross-Cultural Aspects - ROMANOVA, Irina Matveevna; NOSKOVA, Elena Viktorovna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article points out that the consumers' preferences while choosing marketing communications depend to the great extend on the peculiarities of the target audience. The defining criteria for the target audience are age, lifestyle of consumers and cultural peculiarities of the individuals. The aim of this investigation is the developing of the methodological approach and tools for the assessment of cross-cultural peculiarities influence on the students' attitude to the types of marketing communications (advertising (TV and outdoor)), sales promotion, public relations, personal sales, network communications). During the investigation we defined the influence of different elements of the culture model (cultural values, elements of material and institutional environment) on the Russian and Chinese students' attitude to the marketing communications. We defined the discontinuities in consumers' behaviour which are conditioned by the cross-cultural peculiarities. This is of great interest for the market operators when developing the programmes of sales and services promotion, oriented to the given target audience.
Keywords: marketing communications; cross-culture; culture model; advertising